Comparative study of macroeconomic variables towards unemployment in Malaysia and Thailand / Norhafizah Abdul Malek - Abdul Malek, Norhafizah (Faculty of Business Management, 2017)
Unemployment is a key macroeconomic indicator that will determine the health of an economy. Unemployment can be defined as a phenomenon that occurs when a person who is actively searching for employment is unable to find work especially fresh graduates. Unemployment is considered as a problem due to its give various impact to the society. For example, if there is high unemployment in some countries, the possibility of people to involve in crime will also be high. This is because people who are unemployed tend to do the crime in order to support themselves to live in the country. There are several sources of data that are used to complete this research such as electronic sources which can be collected from the e-sources that can be found in the web of library UniversitiTeknologi Mara (UiTM) such as Datastream, World Bank data and database online that have been subscribe by UiTM. Besides that, journals and articles are also sources of the data which can be found in ScienceDirect, Emerald Premium and Proquest. In addition, the data and some information also can be found in the Internet which used as a supporting material.The result ofanalysis will be obtained through research by using Stata for interpreting data, Microsoft Excel for combining data, and Google to search supporting documents. Method that will apply is Multiple Linear Regressions (Panel Data). Fixed Effect Model was usedto determine the relationship between unemployment with Gross Domestic Product, Interest Rate, Inflation Rate and Exchange Rate. In order to run Fixed Effect Model, we must run the f-test for fixed effect and Breusch Pagan LM test first. Then, we can decide to run Fixed Effect Model by using Least Square Dummy Variable (LSDV). The result in LSDV will be used to indicate the relationship of unemployment with GDP, interest rate, inflation rate and exchange rate. It means that all the independent variable in this study will influence the unemployment rate in both countries, Malaysia and Thailand. Any movement in all the independent variable will effected the unemployment in both countries.